Evolution of Gas Desorption Hysteresis in Coal under Negative-Pressure Condition Attenuation Mechanism and an Intuitive Index - Wei, Yushan (Langmuir : the ACS journal of surfaces and colloids, 2025)
Quantifying the extent of desorption hysteresis is essential for establishing gas flow models. However, existing indices fail to adequately represent the changes in the actively mobile gas volume involved in transport, and experiments on the degree of hysteresis in negative-pressure environments are scarce. Therefore, this study conducted isothermal adsorption and desorption tests under both atmospheric- and negative-pressure conditions. Based on the results, a segmented gas desorption model was developed, introducing a new hysteresis index. The study examined gas desorption characteristics under negative pressure in coal and its effect on the maximum gas flow volume. The key conclusions are as follows: The study employed various pore testing methods, revealing well-developed micropores in the Shunhe coal sample and the existence of a certain amount of ink-bottle-shaped pores. Isothermal adsorption-desorption experimental results indicated significant desorption hysteresis effects in both the particle and column samples. The study defined a new index termed the active gas index (AGI) to characterize the actively mobile gas volume participating in desorption, which is the ratio between the active gas quantity participating in desorption and the theoretical value of gas migration capable of participating in flow. The AGI values increase with the increase of pressure drop under both atmospheric- and negative-pressure conditions. The rate of change of AGI in the atmospheric section is relatively flat but increases rapidly upon entering the negative-pressure environment. The evolutionary trend of the AGI can better reflect the characteristics of the change in the active gas volume during negative-pressure desorption. This research provides a new perspective, holding significant theoretical value for shale gas and coalbed methane development